Sky Lanterns And Aviation Safety : A Study At The Mae Fah Luang Chiangrai Airport - Charoensook, Chartchai (International Journal of Engineering and Technology, 2018)
The purpose of this research is to study explore the challenges emerging due to use of sky lantern at the Mae Fah Luang Chiangrai Airport, which has threat to aviation safety. The current pertaining is qualitative research done by in-depth interview of aviation personnel at Chiangrai Airport. The finding of the study can be summarized as follows:Â 1) Lantern obstructs visibility of flight path posing challenge to both pilot and air traffic controller.Â 2)Â Lantern can accidentally slip into aircraft engine and it could jam the engine or could cause engine explosion.Â 3)Â Lantern slips into aircraft controlling equipment, this could cause aircraft unable to control its direction.Â 4)Â Lantern that floats and sticks with aircraft body, could cause fire to aircraft body.Â 5)Â Lantern that falls onto runway or airport drive way, may endanger aircraft while takeoff and landing or it could damage aircraft during taxiing on the runway. However, it is opined by respondent to jointly organize community awareness campaign to educate people and mitigate the associated threat. Â